CONFORMATIONAL EQUILIBRIUM AND SPECTROSCOPIC PROPERTIES OF CALIX[4]ARENE: THEORETICAL STUDY USING AB INITIO METHOD - Hanggara Sudrajat; Ria Armunanto (Indonesian Journal of Chemistry, 2008)
Molecular structures were optimized for the calix[4]arene by ab initio method at the Hartree-Fock level of theory using LANL2DZ and 6-311G basis sets. Conformational equilibrium of four calix[4]arene conformers are reported. The results are compared with experiment, force field, and semiempirical molecular orbital calculations. General trends in relative stabilities of calix[4]arene decrease in following order: cone > partial-cone > 1,2-alternate > 1,3-alternate. The most stable conformer is the cone conformer that is stabilized by an array of four hydrogen bonds and these results agree with the reported experimental observations. All structures were analyzed using theoretical IR, UV-Vis, and 1H NMR spectra attributed to the conformational equilibrium at the Hartree-Fock level of theory using LANL2DZ basis set.